Impact of fragmented habitats on reproductive success in dominant shrubs: natural selection on floral display and pollinator visitation - Chen, Min; Wang, Zheng-jiao-yi; Ma, Xu-jun; Zhao, Xue-yong (Frontiers in Plant Science, 2025)
Flowering shrubs in fragmented habitats often experience pollen limitation, which can lead to strong natural selection on floral display and affect reproductive success. Effective management and protection of dominant shrubs in fragmented habitats require a thorough understanding of the factors driving plant reproduction. However, the impact of fragmented habitats on reproductive success through floral display and pollinator visitation has not been experimentally quantified. We examined pollen limitation by comparing female fitness between open-pollinated and hand-pollinated plants. We also assessed the impact of natural selection (β) on floral display by comparing natural selection gradients in plants from natural and fragmented habitats. Our results show that this species is pollen-limited, with supplemental pollen increasing female fitness by 32%. This species exhibits directional selection for more open flowers and longer keel petals. We found that the number of open flowers is the main factor influencing pollinator visitation frequency and female fitness, and that pollinator visitation positively affects female fitness. This study provides insights into how fragmented habitats influence linear selection gradients related to the number of open flowers. Furthermore, this study highlights that fragmented habitats significantly influence reproductive success, with floral display being a crucial factor to consider when designing conservation strategies for this population.